Effects of ohmic heating technology in chemical properties of foods - Pereira, Ricardo (2006)
In this work some food products where characterised chemically before and after ohmic and conventional heating treatments, comparing both processes. In each food type (cloudberry jam, goat milk) pH was measured and parameters such as total and volatile solids, ash, titratable acidity, ascorbic acid, total sugars, total fatty acids, total phenolic compounds and anthocyanins content were determined, depending on the food being analysed. In goat milk samples treated by ohmic technology, the titratable acidity 0.12 % (as lactic acid), pH value 6.59 and total fatty acids content in milk fat 86.5 g 100gˉ¹ were comparable to those found in milk treated by conventional process. In cloudberry jam samples treated by ohmic technology the results of some of the main parameters tested, such as total sugar content 47.4 g 100gˉ¹, ascorbic acid concentration 2.8 g 100gˉ¹ and titratable acidity 6.01g 100gˉ¹ (as citric acid) did not show significant differences for samples treated by conventional technology.